On 2-Primal Quinary Semiring and its Characterizations by Special Subsets - Tuhfatul Janan (Department of Mathematics, Hasanuddin University, 2025)
In this research, we introduce a new concept of 2-primal quinary semiring and its characterizations by utilizing special subsets. This concept is a generalization of 2-primal ternary semiring. The method of this research is a literature study on scientific articles in international journals. This research starts from concept of quinary semiring and some its ideals, then continues by studying the basic concept of 2-primal quinary semiring, including weakly and strongly nilpotent sets. Next, we define some special subsets of quinary semiring, and then provide some of their properties. Through this special subsets, we provide characterizations of 2-primal quinary semiring.